Justice Sector Reform in Mongolia : Looking Back, Looking Forward - Gramckow, Heike (World Bank, Washington, DC, 2014)
The justice sector in Mongolia has changed significantly in the 20 years since the country became a democracy. From the very beginning, the World Bank and other international partners have provided significant assistance to reform processes, particularly in areas concerned with the development of an independent judiciary. Especially in comparison to other countries in the region, Mongolia's reform efforts have been generally successful. During the early and economically difficult times since democracy was established, reform activities naturally focused on legal reforms, including the creation of a legislative framework for democratic institutions, the transition to a market economy, and for needed changes in the relationship between the state and the people. This was followed at the end of the millennium by concerted efforts to reform justice institutions and to improve human capacities for supporting, implementing and sustaining reforms. Mongolia was the first developing nation to pursue comprehensive and inclusive strategic planning for its justice sector. Its strategic plan has provided a roadmap for reforms over many years and withstood leadership changes in both the government and in the key justice agencies. Much has been achieved, considering the challenges that have been overcome in terms of justice system infrastructure, human capacities and changes in attitudes, all with only very limited budget resources. At the same time, reform gaps exist and public trust in the justice sector is lacking. Critics continue to point to weak and uneven decision making capacities of prosecutors and judges, despite more than a decade of intensive donor support for their training. This paper reviews some of the underlying issues affecting justice reforms in Mongolia; and points to areas that require attention to overcome the current shortcomings and challenges.